Heterogeneous Multiple Bank Financing Under Uncertainty: Does it Reduce Inefficient Credit Decisions? - Christina E. Bannier (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2005)
Small and medium-sized firms typically obtain capital via bank financing. They often rely on a mixture of relationship and arm's-length banking. This paper explores the reasons for the dominance of heterogeneous multiple banking systems. We show that the incidence of inefficient credit termination and subsequent firm liquidation is contingent on the borrower's quality and on the relationship bank's information precision. Generally, heterogeneous multiple banking leads to fewer inefficient credit decisions than monopoly relationship lending or homogeneous multiple banking, provided that the relationship bank's fraction of total firm debt is not too large.
Keywords: G21; D82; L14; 330; Relationship lending; Uncertainty; Asymmetric information; Credit; Finanzierungstheorie; Kredit; Bank; Risikomanagement; Entscheidung bei Unsicherheit; Asymmetrische Information; Lieferanten-Kunden-Beziehung; Theorie